New sprinkler arrangement for UiTM’s Stadium field / Nur Lina Abdullah … [et al.] - Abdullah, Nur Lina; A Kadir, Norhidayah; Sadikin, Zubaidah; Harun, Nurzalina (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
The purpose of this project is to study the arrangement of water sprinkler at Universiti Teknologi MARA(UiTM), Shah Alam stadium field. There are 35 number of sprinklers used with 7X5 arrangement. The current problem is that as there are too many sprinkler used, the overlapping area becomes too large and hence leads to waste. In order to minimize the number of sprinklers used as well as the overlapping area, new arrangement of sprinklers is proposed. The validity of the developed arrangement is tested by using Microsoft Excel and mathematical software, MAPLE 14. Finally, there are six possible arrangements that can be used to replace the current arrangement.